2001
DOI: 10.1109/42.918474
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low-contrast detail perception on storage phosphor radiographs and digital flat panel detector images

Abstract: A contrast detail analysis was performed to compare perception of low-contrast details on X-ray images derived from digital storage phosphor radiography and from a flat panel detector system based on a cesium iodide/amorphous silicon matrix. The CDRAD 2.0 phantom was used to perform a comparative contrast detail analysis of a clinical storage phosphor radiography system and an indirect type digital flat panel detector unit. Images were acquired at exposure levels comparable to film speeds of 50/100/200/400 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Even DR obtained with 50% less dose was still found to be superior for structures in the high attenuation areas of the mediastinum, while most structures in the lung were judged equivalent. Our results are concordant with those reported by Peer and co-workers, who also found, in a contrastdetail experiment, that the advantages of DR over CR are particularly apparent for the delineation of low-contrast structures at lower dose levels [5]. The performance differences we found in that subjective preference study favor more strongly the DR system compared with the results of the previously reported phantom study [11].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Even DR obtained with 50% less dose was still found to be superior for structures in the high attenuation areas of the mediastinum, while most structures in the lung were judged equivalent. Our results are concordant with those reported by Peer and co-workers, who also found, in a contrastdetail experiment, that the advantages of DR over CR are particularly apparent for the delineation of low-contrast structures at lower dose levels [5]. The performance differences we found in that subjective preference study favor more strongly the DR system compared with the results of the previously reported phantom study [11].…”
Section: Discussionsupporting
confidence: 95%
“…A multitude of studies has been performed in recent years, which all showed substantial potential for dose reduction [1][2][3][4][5][6][7][8][9]. The amount of dose reduction, however, varied between 20 and 50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…88,[105][106][107] Contrast-detail analysis is an efficient means to complete these studies, since a given C-D plot often requires only a single image and minimal time commitments by professional readers. Some C-D studies in radiography seek to optimize the tradeoff between image contrast and x-ray dose to the patient by extending the analysis to include total dose levels.…”
Section: Contrast-detail Analysis In Medical Imagingmentioning
confidence: 99%
“…This technique was introduced to medical imaging in the 1970's and has since been used extensively for CT 78-81 magnetic resonance imaging, 82 ultrasound, 83 mammography, 84,85 fluoroscopy, 86 whole body x-ray systems, 87 as well as imaging displays. 88,89 This technique is used to quantify the combined performance of the imaging system and the image reader in detecting objects representing a clinically relevant range of sizes and contrasts within a domain, focusing on assessing the lower limits of each possible range. 90,91 A C-D graph of minimum detectable contrast level for all sizes of objects provides limiting data on two major regimes of system operation, namely 1. the spatial resolution for high contrast objects ͑high contrast, small object size͒, and 2. the lower level of contrast detectable for larger-sized objects.…”
Section: Contrast-detail Curvesmentioning
confidence: 99%